Challenges And Opportunities For Implementing Midwifery Information Systems In Remote Areas - Sherly Agustini (Rey Media Grafika, 2025)
Maternal and child health is a top priority in Indonesia's healthcare system, especially in remote areas that face limited access, medical personnel shortages, and inadequate healthcare facilities. The implementation of a midwifery information system based on information technology is a potential solution to improve the quality of maternal and neonatal healthcare services. However, the adoption of this system still encounters various challenges, such as limited technological infrastructure, lack of training for healthcare workers, and internet accessibility issues. This study aims to analyze the challenges and opportunities in implementing a midwifery information system in remote areas using a qualitative descriptive approach. Data were collected through literature studies and interviews with midwives, health department officials, and healthcare information system developers. The results indicate that despite significant obstacles in implementing the midwifery information system, opportunities such as mobile applications, cloud-based systems, and integration with national health systems can enhance the efficiency of midwifery healthcare services. Government policy support and capacity-building programs for healthcare workers are key factors in the successful implementation of this system.